What Makes High-Achiever Students Hard to Improve Their Speaking Skill? Apa yang Membuat Siswa Berprestasi Sulit untuk Meningkatkan Keterampilan Berbicara mereka? - Irmawati, Dini Kurnia (JEES (Journal of English Educators Society), 2016)
Speaking problems do not only happen to low achiever students. High-achiever students with high average score (above 90) also still have speaking problems. This makes the researcher find it important to investigate what factors that make them still get difficulties in speaking. This research is a descriptive study. The subjects include 9 high-achiever students majoring in English Department that have been selected from University of Brawijaya, State University of Malang, and Kanjuruhan University. The data have been collected by using questionnaire, interview guide, and observation sheet. The findings show that the most hampering factor in relation to teaching and learning activities is too many assignments given. Next, in terms of teaching and learning materials, the highest hampering factor is the level of difficulty of the materials which are too high. Also, the most hampering factor related to lecturers’ personalities is that the lecturer is too serious in handling the class. Moreover, lack of English usage is the next highest hampering factor about the use of English as a medium of instruction in class. Also, lack of feedback given to high-achiever students is the most hampering factor of their speaking skill. The findings indicate that preliminary study and need analysis are needed in order to help lecturers teach high-achiever students more effectively which can result in helping them overcome their speaking problems and improve their speaking skill.